Knowledge and Experience of Postnatal Women on Respectful Maternity Care During Childbirth in Selected Health Facilities in Nigeria (2022)
Respectful Maternity Care (RMC) is a lifesaving strategy that encompasses respect for women's basic human rights that includes respect for women's autonomy, dignity, feelings, choices, and preferences. However, the lack of RMC limits maternal health service utilization. It is against this background that this study examines knowledge, experience and satisfaction of women on RMC in selected health facilities in Ibadan. This descriptive cross-sectional study employs a simple random sampling technique to select 151 participants. A self-administered questionnaire with a reliability coefficient of 0.78 was used for data collection. Data collected were analyzed using descriptive statistics and chi-square for hypotheses testing at p<0.05. The findings show that respondents' mean age is 28.60 (+5.914) years. Less than half 69 (45.7%) of them have tertiary education and most of the respondents 89 (58.9%) have one or 2 children. A greater proportion of them, 112 (74.2%) have a positive experience of RMC. Majority, 102 (67.5%) of the respondents are highly satisfied with the RMC received. The respondents' experience of care is found to have a strong influence on their subsequent patronage of the health facilities at (2 8.9351, p= 0.011). Their level of knowledge about RMC is not associated with the experiences of the care they received (x2=6.383, p=0.567). Given the above, efforts should be made to improve the provision of Respectful Maternity Care in order to enhance the use of skilled care at childbirth. This will enhance the achievement of safe motherhood thus preventing maternal mortality and morbidity.